Prenatal ultrasound heating influences on fetal weight assessment of Oryctolagus cuniculus throughout pregnancy - Ahmad Zaiki, Farah Wahida; Md Dom, Sulaiman; Abdul Razak, Hairil Rashmizal; Hassan, Hamzah Fansuri (SERSC, 2013)
The aim of this in vivo experimental study is to determine the association between ultrasound exposure time and Oryctolagus cuniculus’s fetal weight. A total of 14 pregnant does were exposed to ultrasound heating for 30, 60, and 90 minutes at each gestational stage. Meanwhile, another group of 4 pregnant does served as control, making it a total of 136 fetuses’ weight that were analyzed. There were significant differences in fetal weight during 1st, 2nd and 3rd trimester of pregnancy between groups with different length of ultrasound exposure time. There were also fair correlation and association between groups with different length of ultrasound exposure time and fetal weight during 1st and 3rd trimester of pregnancy. This study suggested that the heating effects of ultrasound exposure might affect the Oryctolagus cuniculus’s fetal weight. Therefore, there should be a rising concern in the awareness towards the negligible effects produced from prenatal ultrasound exposure as it is widely applied during pregnancy in humans.